sqrt(3x+1)-2=6

Simple and best practice solution for sqrt(3x+1)-2=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for sqrt(3x+1)-2=6 equation:


Simplifying
sqrt(3x + 1) + -2 = 6

Reorder the terms:
qrst(1 + 3x) + -2 = 6
(1 * qrst + 3x * qrst) + -2 = 6
(1qrst + 3qrstx) + -2 = 6

Reorder the terms:
-2 + 1qrst + 3qrstx = 6

Solving
-2 + 1qrst + 3qrstx = 6

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 1qrst + 2 + 3qrstx = 6 + 2

Reorder the terms:
-2 + 2 + 1qrst + 3qrstx = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 1qrst + 3qrstx = 6 + 2
1qrst + 3qrstx = 6 + 2

Combine like terms: 6 + 2 = 8
1qrst + 3qrstx = 8

Reorder the terms:
-8 + 1qrst + 3qrstx = 8 + -8

Combine like terms: 8 + -8 = 0
-8 + 1qrst + 3qrstx = 0

The solution to this equation could not be determined.

See similar equations:

| 2(3x-4)=#x+1 | | 2x+22=4x | | (120-85)=x | | 8x-8=8x-1 | | 20-g=-19+2g | | 45x=9x^2 | | 0=-10y-2x | | x/507+6-6=715 | | -16x^2+68x+4=20 | | 20-12n+20=-20-2n | | -x^2+15x-56=0 | | 3b+2a=22 | | 5Y-65Y=200 | | 20b+16= | | -9b+16=-11b | | 5y^3(5y^2-7y+9)= | | 4+.20P=5+30P | | YZ=0 | | .66+.75x=.83 | | 3y-x-3=0 | | y=4x^2+32x+61 | | -4r+2=-5r+10 | | 2(y-3)=2y-9+y | | -7a-3=9+6a | | 0.4x+9.6=7.8 | | -9p+2=-7p-5-3p | | 7+2(5k+4)=-21-2k | | 5n+2=-14-n | | 18x^3=21x^2+72x | | 32m=64 | | 0.6x-1.5=8.1 | | -2m=9-5m |

Equations solver categories